The influence of work ethic, organizational commitment, and self-actualization on employee performance at PT. Dipo Internasional Pahala Otomotif - Hutagalung, Calvin; Rahayu, Cindy; Thedora, Hanny; Cenneth, Reynard Nathaniel; Rostina, Cut Fitri; Fauzi, Fauzi (Privietlab, 2024)
This study aims to evaluate the impact of work ethic, organizational commitment, and self-actualization on employee performance. The research adopts a descriptive quantitative approach, with data collection conducted through questionnaires distributed to company employees. The study sample comprises 40 employees, while validity and reliability tests were conducted with 30 respondents. The validity and reliability tests, along with the plot test involving 30 respondents, met the criteria, with values exceeding 0.05 and Cronbach's alpha above 0.60. Data analysis was performed using multiple linear regression. The results of the simultaneous determination coefficient test (F-test) revealed an F-value of 11.178, which is higher than the F-table value of 2.87, with a significance value (Sig) of 0.000, indicating a positive and significant influence of work ethic, organizational commitment, and self-actualization on employee performance. Partially (t-test), work ethic and organizational commitment were found to have a positive and significant effect on employee performance, while self-actualization did not show a significant impact. Additionally, the determination coefficient test results indicated that the influence of work ethic, organizational commitment, and self-actualization on employee performance accounts for only 43.9%, with the remaining 56.1% influenced by other variables.